Gaspar Melchor de Jovellanos y Bernardo Darquea: Documentos sobre la explotación de la canela en la audiencia de Quito - Paniagua Pérez, Jesús (Estudios humanísticos. Historia, 2002)
During the final years of the eighteenth century, a terrible earthquake destroyed many of the towns in the corregimientos of Ambato and Riobamba, in the hinterland of the Audiencia of Quito. The corregidor of the former proved to be incapable of dealing with the situation, and in his place Bernardo Darquea, an old collaborator of Pablo de Olavide in Spain, was named corregidor. He was charged with, among other things, studying the possibility of reactivating cinnamon exploitation in Amazonia, a theme that Jovellanos had already dealt with in 1797. The two documents that we present in this piece are the result of those invesitigatios.